Two isoforms of Serpent containing either one or two GATA zinc fingers have different roles in Drosophila haematopoiesis. - Waltzer, L.; Bataille, L.; Peyrefitte, S.; Haenlin, M. (The EMBO Journal, 2002)
serpent (srp) encodes a GATA transcription factor essential for haematopoiesis in Drosophila. Previously, Srp was shown to contain a single GATA zinc finger of C-terminal type. Here we show that srp encodes different isoforms, generated by alternative splicing, that contain either only a C-finger (SrpC) or both a C- and an N-finger (SrpNC). The presence of the N-finger stabilizes the interaction of Srp with palindromic GATA sites and allows interaction with the Friend of GATA factor U-shaped (Ush). We have examined the respective functions of SrpC and SrpNC during embryonic haematopoiesis. Both isoforms individually rescue blood cell formation that is lacking in an srp null mutation. Interestingly, while SrpC and SrpNC activate some genes in a similar manner, they regulate others differently. Interaction between SrpNC and Ush is responsible for some but not all aspects of the distinct activities of SrpC and SrpNC. Our results suggest that the inclusion or exclusion of the N-finger in the naturally occurring isoforms of Srp can provide an effective means of extending the versatility of srp function during development.